Pengaruh Sumber Daya Manusia, Standar Akuntansi Pemerintah dan Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan Pemerintah Daerah pada Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD) Kabupaten Manokwari - Sandi H. Pasaribu (Universitas Serambi Mekkah, 2023)
Financial reports are products produced by accounting diciplines as a form of responsibility for the presentation of financial statements. Report Regional Government Finance (LKPD) is intended to meet general objectives fincancial reporting, as well as to meet the special needs of users. This study aims to determine the effect of government accounting standards, internal control system, human resource competency and style leadership on the quality of local government financial report. Sample used in this study BPKAD in Manokwari District, Method sampling used is purposive sampling with a sample as many as 50 respondents. Hypothesis testing is done by using analysis multiple regression. The results showed that human resources, government accounting standards and internal control system have a positive effect on the quality of local government financial reports.